Labour market transitions and wage dynamics in Europe - Jose M. Arranz; Maria A. Davia; Carlos Garcia-Serrano (University of Essex, Institute for Social and Economic Research (ISER), 2005)
Using longitudinal data on individual workers from six European countries for the period 1995-2001, the authors analyse empirically the relationship between labour market transitions and wage growth; in particular, whether transitions across states in the labour market have any significant influence on wage dynamics and the size of this influence. In addition to the incidence of unemployment and inactivity spells on wages, the effects of the duration of job interruption, the time elapsed since job ending and the reasons for job interruption are analysed as well.
Keywords: 330